The Effectiveness of Gamification-Based English Learning and Mobile-Assisted Tools for University Students in Tulungagung - MOCHAMAD ARDI SETYAWAN (Universitas Islam Balitar, 2026)
The integration of digital technology in higher education has encouraged innovative approaches to English language teaching, particularly through gamification and Mobile-Assisted Language Learning (MALL). This study aimed to examine the effectiveness of gamification-based English learning integrated with mobile-assisted tools in improving university students’ English learning achievement and motivation. Mixed-methods quasi-experimental design employing a non-equivalent control group pre-test–post-test model was adopted. The participants were 60 undergraduate students enrolled in a compulsory English course, divided into an experimental group receiving gamified mobile instruction and a control group receiving conventional teacher-centered instruction. Quantitative data were collected using achievement tests and a Likert-scale motivation questionnaire, while qualitative data were obtained through classroom observations and semi-structured interviews to explore students’ learning experiences. Statistical analysis showed that the experimental group obtained significantly higher post-test scores and motivation levels than the control group (p < .05). Qualitative findings further indicated that students perceived the gamified mobile activities as more interactive, engaging, and flexible, which encouraged active participation, collaboration, and autonomous practice beyond the classroom. Overall, the integration of gamification and mobile technology enhanced both cognitive outcomes and affective engagement. These results suggest that gamified mobile learning can serve as an effective and practical alternative instructional strategy for improving English language learning in higher education settings. Therefore, the approach offers valuable pedagogical implications for lecturers seeking to increase participation, motivation, and measurable performance while maintaining flexibility and accessibility for diverse learners across varied instructional contexts and technological infrastructures within contemporary university English education environments today widely globally.